(untitled) (Research, Society and Development, 2021)
Introduction: The perspective for patients with cleft lip and/or palate (CLP) is important in assessing treatment outcomes and contributing to a better quality of life. Objectives: To evaluate the influence of treatment patients’ quality of life with CLP using CLEFT-Q. Methods: Observational cross-sectional study, with 100 individuals attended in a CLP Service. Results: The mean age of the sample was 16±4.9 years. The most frequent cleft type was cleft lip/palate and the most prevalent, transforamen (85%). The treatments performed were: cheiloplasty, palatoplasty, bone grafting, rhinoplasty and orthodontic treatment. The lowest Cleft-q scores were in Appearance and related to appearance of nose and nostrils while the highest were observed in Quality of life Scales as psychological and school. There was a statistically significant correlation between treatments performed and at least one Scale of Appearance, Quality of Life and Facial Function, except for rhinoplasty. Orthodontic treatment showed a negative correlation with the three domains, and the association was statistically significant in Face, Nostrils, Teeth, Lips, Difficulty Speaking, School, Social and Speech Scales, except for Nostrils, Psychological and Eating/Drinking. The speech scale showed statistically significant correlation with palatoplasty, bone grafting and orthodontic treatment and eating/drinking scale showed statistically significant correlation only with bone grafting. Conclusions: The results suggests that the patients studied were dissatisfied with their facial appearance, especially regarding nose, nostrils and teeth. All treatments impacted the patients’ perception of their appearance, health-related quality of life and facial function. Cheiloplasty and bone grafting had a positive impact on patients’ quality of life.